Pengaruh Metode Pembelajaran Picture and Picture terhadap Motivasi dan Pemahaman Konsep Siswa - Sapriawan, Sapriawan; Hermawan, Hermawan (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2022)
There are still many teachers who use a monotonous method when teaching. The use of monotonous methods causes students to be less active, become bored and not serious in following lessons, so that students' motivation and learning outcomes are low. This study aims to determine the effect of the picture and picture learning method on the motivation and understanding of the concepts of seventh grade students of SMP Negeri 1 Sakra in the 2018/2019 academic year. This type of research is quasi-experimental. The population in this study were seventh grade students of SMP Negeri 1 Sakra. Samples were taken using a saturated sampling technique, namely class VII B as the experimental class and VII A as the control class. The results showed that at the first meeting in the control class, the percentage of students' learning motivation was 70.69%, while at the second meeting the percentage was 73.05% with the same category of high motivation. The results of the questionnaire on learning motivation in the first meeting in the experimental class were 76.38%, at the second meeting the percentage was 76.33% including the same category of high motivation. Concept understanding data is seen from the acquisition of pre-test and post-test scores. The average value of the control class students at the time of the pre-test was 27.88 the percentage of 5% with the category of a small percentage of students understanding the concept. Then the average score of students at the time of the post-test was 48.14 with a percentage of 22% in the category of a small percentage of students understanding the concept. The average value of the experimental class students at the time of the pre-test was 29.25, the percentage of 11% with the category of a small percentage of students understanding the concept. Then the average score of students at the time of the post-test was 63, a percentage of 78% with the category of almost all students understanding the concept. The data on psychomotor learning outcomes for the control class at the first meeting was 68.88%, at the second meeting 63.33% in the quite skilled category. Then the experimental class at the first meeting was 79.16% at the second meeting at 78.47% with the same category, namely skilled. The post-test data were then analyzed using t-test, obtained tcount > ttable, or 112.4 > 1.98, so it can be concluded that there is an effect of picture and picture learning method on students' motivation and understanding of concepts.